Practical aspects of demand and capacity evaluation of RC members in the context of EC8-3. - Romao, Xavier (Earthquake engineering & structural dynamics.)
The structural safety assessment procedures proposed in Part 3 of Eurocode 8 (EC8-3) for the case of reinforced concrete structures are addressed. The practical evaluation of the member chord rotation demand according to EC8-3 is examined in detail along with several alternative formulations. The need for these formulations is demonstrated by presenting example situations where the EC8-3 proposal is difficult to apply. The effectiveness of the proposed approaches is assessed through an example application and recommendations for their practical use are defined. Given the importance of the shear span in this context, a sensitivity analysis of the EC8-3 capacity models with respect to this parameter is carried out and discussed in a later section. This analysis aims to assess the validity of the simplifications proposed by a previous research study for the quantification of the EC8-3 capacity values.